2019
DOI: 10.1002/pits.22315
|View full text |Cite
|
Sign up to set email alerts
|

Teaching style and academic achievement: The mediating role of learned helplessness and mastery orientation

Abstract: Although several studies have investigated the roles of teaching practices during the learning process on students, the role of school learned helplessness (LH) and mastery orientation (MO) has not been deeply examined. The present study aimed to verify the dynamics between academic achievement and the perception of the students of their teacher's psychological control and autonomy support by examining the mediating role of school LH and MO. Results confirmed that perceived teacher psychological control can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 53 publications
2
44
1
2
Order By: Relevance
“…Students' academic performance in a learning environment that encourages autonomy discovery is better than their performance in a high anxiety environment (Ramsden and Entwistle, 1981 ). Oriol-Granado et al ( 2017 ) demonstrated that students' positive emotions and autonomy support had a predictive effect on students' academic performance, self-efficacy and academic engagement, and Filippello et al, 2020 ) also demonstrated that teachers' autonomy support had an impact on students' academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Students' academic performance in a learning environment that encourages autonomy discovery is better than their performance in a high anxiety environment (Ramsden and Entwistle, 1981 ). Oriol-Granado et al ( 2017 ) demonstrated that students' positive emotions and autonomy support had a predictive effect on students' academic performance, self-efficacy and academic engagement, and Filippello et al, 2020 ) also demonstrated that teachers' autonomy support had an impact on students' academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Helplessness is also associated with obsessive‐compulsive disorder (Sun, Zhanjiang, Buys & Storch, 2015), psychological inflexibility (Trindade, Mendes & Ferreira, 2020), job dissatisfaction (Sparr & Sonnentag, 2008; Stengård, Bernhard‐Oettel, Berntson & Leineweber, 2017), suicide ideation (Gençöz, Vatan, Walker & Lester, 2007; Lester, 2012; Lester & Walker, 2007), and is a critical factor in explaining depressive symptoms in fibromyalgia (Palomino, Nicassio, Greenberg & Medina, 2007). Helplessness has been shown to play a role in various contexts, such as in academic achievement (Filippello, Buzzai, Costa, Orecchio & Sorrenti, 2020), internalizing and externalizing problems (Sorrenti, Spadaro, Mafodda, Scopelliti, Orecchio & Filippello, 2019), drug addiction (Shaghaghy, Saffarinia, Iranpoor & Soltanynejad, 2011), and pro‐environmental behavior (Landry, Gifford, Milfont, Weeks & Arnocky, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a supportive environment strengthens self-realization and can facilitate positive functioning among adolescents within schools (Reeve and Jang, 2006;Filippello et al, 2019a). On the contrary, a thwarting context, characterized by pressure and coercion that makes individuals feel inadequate and emotionally disconnected, favors maladjustment and the development of school HPL (Barber and Harmon, 2002;Soenens et al, 2010;Li et al, 2016;Filippello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%